Real-time outcome monitoring following oesophagectomy using cumulative sum techniques - Roberts, Geoffrey (Baishideng Publishing Group Co., Limited, 2012)
AIM: To examine the feasibility of prospective, real-time outcome monitoring in a United Kingdom oesophago-gastric cancer surgery unit. METHODS: The first 100 hybrid (laparoscopic abdominal phase, open thoracic phase) Ivor-Lewis oesophagectomies performed by a United Kingdom oesophago-gastric cancer surgery unit were assessed retrospectively using cumulative sum (CUSUM) techniques. The monitored outcome was 30-d post-operative mortality, with the accepted mortality risk defined as 5%. A variable life adjusted display (VLAD) was constructed by plotting a graph of cumulative mortality minus cumulative mortality risk on the y axis vs sequential case number on the x axis. This was modified to a zeroed VLAD by preventing the plot from crossing the y = 0 axis - essentially creating two plots, one examining trends where cumulative mortality was higher than mortality risk (i.e., worse than expected outcomes) where y > 0, and vice versa. Alert lines were set at y = ± 2. At any point where a plot breaches an alert line, it is felt that the 30-d post-operative mortality rate has deviated significantly from that expected and an internal review should be performed. RESULTS: One hundred cases were assessed, with a mean age of 66.4 years, mean T stage of 2.1, and mean N stage of 0.48. Three cases were commenced using a laparoscopic technique and converted to open surgery due to technical factors. Median length of inpatient stay was 15 d. The crude 30 d mortality was 5% and the incidence of clinically significant anastomotic leak was 6%. The VLAD demonstrated a plot of cumulative mortality minus cumulative mortality risk (i.e., 5% per case) which remained in the range -1.4 to +0.5 excess mortalities. With the alert set at two greater or fewer than predicted mortalities, this method does not approach the point of triggering internal review. It is however arguable that a run of performance that is better than expected, causing the plot to be well below y = 0, would mask a subsequent run of poor performance by requiring a rise of greater than two excess mortalities to trigger the alert line. The zeroed VLAD removes this problem by preventing the plot that is examining above expected mortality from passing below y = 0, and vice versa. In this study period, no audit triggers were reached. It is therefore possible to independently assess runs of good, or poor performance and so target internal audit to the appropriate series of cases. It is important to note this technique allows targeted internal review, in response to both above and below average outcomes. This study has demonstrated the feasibility of prospective outcome monitoring using the above techniques, actual real-time implementation has the potential to pick up and reinforce good practices when performance is better than predicted, and provide an early warning system for when performance falls below that predicted. Further development is possible, including more patient specific risk adjustment using the oesophago-gastric surgery physiological and operative severity score for the enumeration of mortality and morbidity score. CONCLUSION: CUSUM techniques provide a potential method of prospective, real-time outcome monitoring in oesophageal cancer surgery.